Non-employed people in the Westpfalz Region (Germany) as target group of continuing higher education: Potentials of a regional demand-orientation - Jessica Neureuther; Dominik Böhmer (REGION, 2020)
Higher Education Institutions (HEIs) and especially continuing higher education has an influence on the development of a region. By focusing on demands of the regional economy as well as its population, these data contribute to the demand-oriented development of study programmes. Therefore, continuing higher education at HEIs is getting more attractive and the participation rate can be enlarged. Another aspect could be the identification of new target groups, for example regional minorities. In this paper, the Westpfalz region (Germany) is considered as an example, as it has interesting characteristics, such as the structural weakness and the participation in further education that is below national average. For this purpose, a representative Regional Population Survey was conducted to describe the population of the Westpfalz region and their educational needs. The group of non-employed people stood out in this survey because of their size and their willingness to participate in continuing higher education. In contrast to the traditional target group of employed academics, the results of the survey show that there are similarities and differences referring to their educational requirements. These results provide evidence that helps to develop and design study programmes especially for continuing higher education that take into account the needs of this target group. At the end of the paper, the potential impact this may have for the Westpfalz region is discussed.
Keywords: 330; continuing higher education; target groups; non-employed people; regionaldevelopment